ANALISIS HASIL BELAJAR SISWA TERHADAP PENGGUNAAN BAHAN AJAR FISIKA TERINTEGRASI AYAT AL-QURAN - Susanti, Erni Dwi; Astuti, Budi (UPEJ Unnes Physics Education Journal, 2020)
This research aims to analyze the increase in learning outcomes of students through the development of integrated Physics teaching material verses of the Quran. This research uses research and development methods (RnD) with one group pretest-posttest design. The research subjects were thirty students of grade XI in SMA Negeri 6 Semarang. Research data was collected using questionnaires and pretest-posttest questions. The materials that have been developed are tested using feasibility test questionnaire by validators and hitch test. The resultt show that the average assessment percentage is 83.07% which is very feasible. For the readability test showing the average score is 76.40% means this teaching material is easy to understand. Based on the test, it can be said that integrated Physics teaching material verses of the Quran are very feasible and easy to understand so that it can be used as a learning source. The increation of learning outcomes with N-gain score is 0.63 shows that using integrated Physics teaching material verses of the Quran can significantly improve student learning outcomes.